Análise da maturidade de empresas que desenvolvem projetos do setor da construção civil com o foco em gestão de desenvolvimento de produtos - Rodrigues, Eloise Wacholski (2015)
Despite the growth of the construction industry over the last years, the work in Brazil are still marked by the lack of quality, delays and losses, excluding its evolution. However the present study aims to present analysis of the maturity level of the project development companies in the Construction sector, through the maturity level model of the product development management of Rozenfeld et al. Therefore, it applied the research survey on companies that develop projects on construction sector in the South region of Brazil. In order to enrich the research it was used discriminant analysis, with the intention of identify the best variables that it differentiate between two groups or more, as well as the stepwise method by the software SPSS (Statistical Package for the Social Sciences). The results showed that companies that develop projects for the construction perform product development process (PDP) activities, and it possess some principles of product development management (PDM), to conduct monitoring of costs and risks, standardized activities, integration projects, change control and still aplly stages of approval concepts. Therefore, it concludes that exist similarity between product development process (PDP) and construction management, however there are some adjustments that shall happen for the implementation of PDP in construction. There was also a considerable adherence of the maturity level model of Rozenfeld et al. with the characteristics of the companies studied, noting that it possess a maturity level at most 2.4 (Intermediate).